Training of Practising Engineers in the Information Use - Vasudeva Rao, K. N. (Journal of Information and Knowledge, 1978)
Emphasises the need for orientation course of engineers in information use. Gives details of the orientation programme given in Central Machine Tool Institute, Bangalore.